2020
DOI: 10.48084/etasr.3943
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fluids – with a Particular Emphasis on Vegetable Oils – as Replacements of Transformer Oil: A Concise Review

Abstract: For many decades transformer oil has served as a well-known insulating medium. Its electrical properties, among others, have been studied in length. In recent years, with the increasing concern for the environment, alternative insulating liquids have been proposed. In the context of this concise review, such alternative fluids are investigated. Some conflicting evidence regarding experimental results that still persist are discussed and aspects of vegetable oils in need of further work are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Ravulapalli S. et al [74] reported that a higher amount of SFA imparted lower oxidative and thermal stability, which eventually leads to a faster deterioration rate. In general, PO consists of 40% of OA (mono-unsaturated fatty acid) and 45% of palmitic acid (SFA) [32]. Some studies also present experimental results of palm oil methyl ester (POME) and palm kernel oil methyl ester (PKOME), which are obtained from the transesterification process.…”
Section: ) Ac Breakdown Voltage Of Palm Oilmentioning
confidence: 99%
“…Ravulapalli S. et al [74] reported that a higher amount of SFA imparted lower oxidative and thermal stability, which eventually leads to a faster deterioration rate. In general, PO consists of 40% of OA (mono-unsaturated fatty acid) and 45% of palmitic acid (SFA) [32]. Some studies also present experimental results of palm oil methyl ester (POME) and palm kernel oil methyl ester (PKOME), which are obtained from the transesterification process.…”
Section: ) Ac Breakdown Voltage Of Palm Oilmentioning
confidence: 99%
“…The idea emerged from the energetic sector, where vegetable oils have been used as a green alternative to mineral insulating oils for transformers, for over twenty years. They offer higher performance (better breakdown voltage, much higher flash points, and fire points) and a better environmental profile (extracted from renewable resources such as plants or seeds, toxic-free, highly biodegradable) [ [21] , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…It is true that their use has improved the dielectric performance of power transformers, as shown by the studies conducted by Perrier et al [9]. However, they still have to meet environmental and cost-competitive requirements because they are non-biodegradable, their use is eight times more expensive than mineral oils [10,11]. In order to overcome the limitations of their uses, researchers have focused on natural esters or vegetable oils [12,13].…”
Section: Introductionmentioning
confidence: 99%